South Sudan : Impact of a Continued Internal Conflict on Food Security and Poverty - Pape, Utz (World Bank, Washington, DC, 2015)
South Sudan is a fragile country beset by conflicts. The oil shutdown accompanied by a border closure in 2012 was resolved, but ongoing military clashes between factions of the ruling party have affected livelihoods since December 2013. Before the onset of these conflicts, large parts of the population were food insecure (2 out of 3 people) and lived in poverty (1 out of 2 people). This note estimates and juxtaposes the impact of the oil shutdown and the ongoing military conflict on livelihoods based on food price changes, predicted harvest losses and displacement. The resulting poverty estimates help to understand the structural implications of these conflicts. But to validate these numbers, test the underlying modeling assumptions and inform a policy response, new data needs to be collected urgently.